Continuity and discontinuity in Early, Middle and Late Neolithic pottery types of eastern Fennoscandia : reflections from Bayesian chronologies - Pesonen, Petro (Helsingin yliopisto, 2021)
The focus of this dissertation is on eastern Fennoscandian Early, Middle and Late Neolithic pottery types and their chronologies. The study presents and evaluates the available radiocarbon dates connected with these types and builds a radiocarbon chronology with the help of Bayesian statistics, i.e. using model building to define the starting and ending boundaries for pottery type phases. The phases are also visualized through summed probability distributions of the radiocarbon dates. Birch bark tar used as a repair material and charred food crust in the pots themselves form the most reliable group materials for deriving radiocarbon dates and are furthermore directly connected to specific pottery types. Several error sources within the corpus of radiocarbon dates are evaluated, and the marine reservoir effect (MRE) is specifically considered problematic for charred crust dates. In the case studies, a MRE correction procedure utilizing stable carbon isotope values to signal the marine content of the crust is reviewed and then used to correct these dates. A salient issue of typology and chronology studies is the identification of the continuity and discontinuity of archaeological cultures, or rather the traditions and influences associated with and maintained by societies. In eastern Fennoscandia, two cases of rapid and widespread migrations now seem to be confirmed by aDNA-studies: those connected with the dispersion of Typical Comb Ware and Corded Ware. On the other hand, the slower dispersion rates and changes seen in other artefact cultures may have been caused by shared societal networks diffusing commodities at a slower pace. It is possible to study these types of cultural continuities, discontinuities, and contemporaneous trends with the help of Bayesian modelling of ceramic type phases. In this work, I have identified the following points of time that can be interpreted as times of disruption or disconnection: 1) the termination of pottery production in the northern parts of eastern Fennoscandia at the end ...